Entre Discursos, Prescrições E Percepções: A (Des)Valorização Do Estatuto Socioprofissional Dos Professores Da Rede Estadual Paulista De Ensino - Silva, Thiago Moreira Melo E [UNIFESP] (2017)
This research analyzes some forms of control and (dis)qualification promoted by the Education Department of the State of São Paulo (SEE/SP), concerning teacher’s work, through reformist discourses and measures. In this sense, this research verifies which factors/instruments have been employed by the government of the State of São Paulo in order to judge the formation and the work of state teachers as insufficient/disqualified. Moreover, this dissertation aims at identifying the concept of “quality” that has been constructed by the SEE/SP over the last years, especially from the 1990s. The Education Department legitimized the States’ aim at a supposed improvement in the formation of its teachers as a condition for enhancing teaching quality. In order to verify the teachers’ perceptions facing the reformist measures set by the educational policies, semi-structured interviews were carried out with teachers, school managers and student coordinators in two State schools in São Paulo. Furthermore the corpus of data is also compound of documents issued by national and international institutions, such as the United Nations Educational, Scientific and Cultural Organization (Unesco), the International Bank for Reconstruction and Development (IBRD), the Organization for Economic Co-operation and Development (OECD), the Ministry of Education and Culture (MEC) and the SEE/SP. The analysis of interviews and documents regarding educational policies is supported by the contributions of Bardin (2010), Fairclough (2001), Scheffler (1974) and Van Dijk (2008). The theoretical frame that grounds this research is based on Ball (1992, 2002, 2005) and Bourdieu (2007, 2008), besides other authors who engaged with similar discussions, as Adrião (2006), Ricardo Filho (2005) and Shiroma; Moraes; Evangelista (2011). As it emerges from the analysed documents, there is a network of legitimacy composed by institutional agents, which is essential for the multilateral agencies to consolidate their proposals for educational policies along with the national States. These agents prescribe the type of formation and work that must be performed by the teachers. The existence of a constant and systematic devaluation and accountability discourse as well as an intervention by the SEE/SP on the teaching work became evident from the analyzed documentation. The source of this legitimization is to be found in the results of external evaluation: those, who do not respond to the logic of productivity and performance established by the State educational policies over the last years, are to be classified as disqualified. Opposing this perception of crisis in the public schools, the pedagogical team and the students’ families expressed satisfaction regarding the teaching work quality in the schools. However, they expressed complaint about the financial and infrastructural difficulties faced by the schools, which affects the educational quality offered. Although the interviewees occasionally criticize the formation and the teaching work, the problems in State Schools in São Paulo were more often associated with an authoritarian and centralized management than with the type of work performed by the professionals working in the field of education.